PENGARUH CITRA PERUSAHAAN DAN KEUNGGULAN PRODUK TERHADAP KEPUASAN NASABAH PADA PRODUK TABUNGAN EMAS: Studi PT Pegadaian UPC HBM Kota Sorong - Hariyanto, Galuh Hesty Putriana; Wijiastuti, Retno Dewi; Rahayu, Agilistya; Sofia, Susetyowati (LP2M Universitas Bina Bangsa, 2025)
This research aims to determine the effect of company image (X1) and product superiority (X2) on customer satisfaction (Y) on gold savings products (PT Pegadaian UPC HBM Study, Sorong City. This research uses a quantitative approach with descriptive methods with a population of 455. Takeaways The sample used non-probability sampling with a purposive sampling technique and sample criteria focused on customers who saved gold savings at PT Pegadaian UPC HBM Sorong City in 2022-2023 so that the number of samples in this study was 215. The results of this research analysis show that the company image ( X1) has a positive and significant effect on customer satisfaction (Y) with a significant value of 0.000 < 0.05 (X1) and product excellence (X2) simultaneously have a positive and significant effect on customer satisfaction (Y) with a significant value of 0.000 < 0.05.